The double connection: towards a bi-directional notion of participation - Devos, Tim; Boelens, Luuk (DISP, 2024)
Self-organised initiatives are increasingly recognised as an alternative to the structural deficit of participatory planning approaches, both in theory and in practice. Nevertheless, public governance is struggling to find ways to deal with such initiatives. This article identifies four prominent categories of self-organised practice, analysing the main motivation to engage in and with these practices, from the perspective of government as well as the self-organised actors. This is in turn linked to three prominent theoretical answers on how governments might deal with self-organisation. Lastly, we reflect on the complexities of a possible double connection between policymakers and self-organisations.